Aspects related to the outcomes of the treatment, in international borders, of cases of tuberculosis as associated to comorbidities - Débora Christina Santos Souza; Keurilene Sutil de Oliveira; Rubia Laine de Paula Andrade; Lucia Marina Scatena; Reinaldo Antonio Silva-Sobrinho (Universidade Federal do Rio Grande do Sul, 2019)
Abstract Objective: analyzing the aspects associated with case outcomes and the international border situation when it comes to patients with tuberculosis (TB) associated with comorbidities. Method: exploratory descriptive epidemiological study, analyzing all new cases of TB with comorbidities reported in 2013 on SISNAN in the cities at the border of the state of Paraná and Paraguay. The variables used were: sociodemographic, clinical and operational. To analyze the data, descriptive analysis and the chi-square test were applied. Results: 227 cases of tuberculosis associated with comorbidities were reported and 70.9% were from cities bordering Paraguay. Alcoholism (22.0%) and AIDS (13.7%) were the most common comorbidities. The chi-square test presented a statistical association of border cities with negative outcomes and not performing directly observed treatments. Conclusion: Through the study, it was possible to find that the location of border cities can be determinant for a negative outcome.